Exploring the contractual incentivization and penalization of professional consultants’ performance in the construction ndustry - Sebola, Morongoa (My University, 2021)
In the construction industry, professional consultants are appointed in a project to provide professional services to deliver the project successfully. However, in contact practice, project deliverables are repeatedly compromised due to consultants' poor performance. The study is aimed at exploring the use of contractual incentivization and penalization as a remedy and motivation for consultants' performance in the construction industry in South Africa. This is because a penalty is a remedy and an incentive is a motivation that has been found to improve performance. Using the mixed-method choice, survey questionnaires were used to collect quantitative data and structured interviews were used to collect qualitative data. The professional opinions of 22 professional consultants in South Africa were collected. The study has used descriptive statistics, Relative Importance Index (RII), Bivariate analysis as well as cross-tabulation to analyze quantitative data whereas Thematic analysis and Content analysis were used to analyze qualitative data with the aid of Microsoft Excel computer software for the analysis. The influence of professional consultants’ performance on a project has been subject to scrutiny. Professional consultants 'poor performance compromises one or more of the project deliverables and ultimately the project performance. The consultant's poor performance traits that were found to have a negative impact on the project are categorized into inadequate input, variation orders, inconsistent documentation, poor flow of information, design issues and inaccurate estimate. These points out that the consultants' performance is an issue in the South African construction industry despite the standard contracts that govern professional service delivery. Therefore, a penalty-incentive payoff model has been developed to improve the consultants' performance. Each incentive/penalty is used to penalize or incetivize each of the main KPIs, that is the Time/Schedule Incentive is adopted to incentivize or penalize Time KPI, Cost Incentive is adopted to incentivize or penalize Cost KPI, Quality Incentive is adopted to incentivize or penalize the Quality KPI and Design Integrity Incentive is adopted to incentive or penalize Sustainability KPI. The incentive and penalties ought to be built in the Professional Service Contract (PSC) pending the nature of the specific project and Key Performance Indicator (KPI) metrics that are important to the project. Also, the adoption of the scorecard system that equally penalizes and incentivizes the specific KPIs should be incorporated into the PCS because using one mechanism is one-sided. The study underlines several areas of improving the professional consultants' performance in the construction industry through the adoption of incentive and penalty mechanisms. Therefore, this study provides apiece of fundamental knowledge and direction for further research to constantly improve the consultants' performance through the implementation of contractual strategies and awareness of the effectiveness of incentives and penalties
A research report submitted to the School of Construction Economics and Management, Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Building in the field of Project Management, 2021